THE USE OF ILLEGIBLE WRITING IN PAINTING - (:unkn) unknown (ANADOLU UNIV, 2016)
This article is going to discuss the approach of how the writing's illegibility takes place in a work by putting the emphasis on writing's representation in visual arts. Writing's presence in plastic arts manifests itself in various ways in art history. When writing loses its relation with language, meaning and content, it finds its place as an element forming up the work with its own plastic. This research, based on the position of the writing's own plastic manifesting itself with the illegible use of itself in a work and its' representation, details the alteration of the writing's place in a work throughout time over a number of artists and different methodic uses.
Keywords: Writing; Painting; Illegible; Representation; Language